Antenatal Endotoxin Impairs Lung Mechanics and Increases Sensitivity to Ventilator-Induced Lung Injury in Newborn Rat Pups - Mandell, Erica W.; Mattson, Courtney; Seedorf, Gregory; Ryan, Sharon; Gonzalez, Tania; Wallbank, Alison; Bye, Elisa M.; Abman, Steven H.; Smith, Bradford J. (Frontiers in Physiology, 2021)
Perinatal inflammation due to chorioamnionitis and ventilator-induced lung injury (VILI) at birth are independent risk factors for the development of bronchopulmonary dysplasia. We have previously shown that antenatal endotoxin causes abnormal lung structure and function in two week old rats, but whether antenatal endotoxin impairs lung mechanics at birth and increases risk for VILI is unknown. Fetal rats were exposed to 10µg endotoxin or saline via intra-amniotic injection. At birth (D0) or 7 days (D7), rats received 90 minutes of lung protective ventilation (PROTECT group; tidal volume (Vt)=6 ml/kg with positive end expiratory pressure (PEEP)=2 cmH20); P20 ventilation (plateau pressure (Pplat)=20 cmH2O, PEEP=0); or P24 ventilation (Pplat=24 cmH2O, PEEP=0, only applied to D7). Prior to prolonged ventilation at D0, endotoxin-exposed rats had decreased compliance and inspiratory capacity (IC) compared to controls. At D7, endotoxin was associated with reduced compliance. High pressure ventilation (P20 and P24) tended to increase IC and compliance in all saline-treated groups. Ventilation at D0 with P20 increased IC and compliance when applied to saline-treated but not endotoxin-exposed pups. At D7, P24 ventilation of endotoxin-exposed pups increased elastance, bronchoalveolar lavage protein content, and IL-1b and TEN-C mRNA expression in comparison to the saline group. In summary, antenatal endotoxin exposure alters lung mechanics at birth and one week of life and increases susceptibility to VILI as observed in lung mechanics, alveolocapillary barrier injury, and inflammatory mRNA expression. We speculate that antenatal inflammation primes the lung for a more marked VILI response, suggesting an adverse synergistic effect of antenatal and postnatal exposures.